AN ANALYSIS OF REGULAR AND IRREGULAR VERBS IN STUDENTS’ ESSAY WRITING - Fitria, Tira Nur (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
The objective of the study is to know the using of regular and irregular verb in the students writing essay, and to know the most dominant verb past written by the students in their students writing essay. The design of this study is qualitative research. Based on the analysis from 14 students writing essay, it shows that the students use both regular and irregular verb (past) in their students writing essay. Both regular and irregular verbs are 312 data in verb 2 (past). In the regular verbs, there are 142 data or 45.51 %, and in irregular verb, there are 170 data or 54.49 %. It shows that the most dominant verb past written by the students in their students writing essay is irregular verb. Regular verbs are verbs that can change according to tense and change it regularly. Regular verbs are verbs whose changes comply with normal rules, that is with add the letter -d or -ed to the verb first-form / verb-1 (infinitive) so that it becomes a verb form second / verb-2 (past tense). There are several things that must be considered in the way of forming regular verbs by adding the letter -ed suffix or -d in the basic verb/verb-1 (infinitive). Irregular verbs are verbs that change according to the tense and do not comply with normal compliance. The past tense Irregular verbs are not formed from basic verbs / verb-1 (infinitives) plus letters -d or -ed letters to form verb-2/past tense. Irregular verbs form their past tense in a different way (through) not always) through a vowel and consonant change. So that, these forms must be memorized by the learners/students.